Exploring interdependent privacy – Empirical insights into users' protection of others' privacy on online platforms - Anjuli Franz; Alexander Benlian (Electronic Markets, 2022)
Recent information privacy research has started to spark a debate about privacy infringements that happen not on an individual, but on a multi-party level. Here, a person's own information privacy is affected by the decisions of others – a phenomenon referred to as interdependent privacy. Building on the 3R Interdependent Privacy Protection Framework, we explore the underlying mechanisms of how and why interdependent privacy violations happen and how they can be remedied. Drawing on an online vignette experiment (N0.167em=0.167em330), we investigate the efficacy of an interdependent privacy salience nudge and reveal that it can decrease the likelihood that users disclose others' personal information by 62%. Furthermore, we develop a novel measurement instrument and empirically validate that users' decision to disclose others' personal information to an online platform is formed via a serial mediation mechanism through users' realization of the data transfer, recognition of others' ownership, and respect for others' rights. We discuss important implications for both theory and practice.
Keywords: O30; D91; 620; Interdependent privacy; Peer disclosure; Online platforms; Privacy nudge; Online vignette study; Serial multiple mediation